Zircon U–Pb, O isotope, and geochemistry study of the early Palaeozoic granitic gneiss in the Dinggye district, central Himalaya: Implications for the early Palaeozoic orogenic event along the northern margin of Gondwana. (8th January 2019) - Zhang, Fan; Wang, Yanbin; Yang, Deting
Abstract : To better constrain the evolution of the early Palaeozoic orogenesis along the northern margin of Gondwana, we present new petrological, geochronological, and geochemical studies of the Cambrian–Ordovician granitic gneiss in the Dinggye area, central Himalaya. The granitic gneiss is medium‐coarse grained, with porphyritic, augen, banded, or gneissic structure, and has undergone strong deformation. The mineral assemblages are quartz, plagioclase, K‐feldspar, muscovite, and biotite, with minor amounts of accessory minerals. The granitic gneiss samples are characterized by high SiO2, Al2 O3, and Rb/Sr contents but low MgO, TiO2, FeOt, and MnO contents, with A/CNK of 1.08–1.38. The REE patterns of the granitic gneiss show high LREE/HREE and negative Eu anomalies. In the trace‐element chondrite‐normalized diagram, the samples show enrichment in LILE (e.g., Rb, Th, U, and K) and depletion in some HFSEs (Nb and Ti). These features indicate that the protolith was a calc‐alkaline and peraluminous S‐type granite. Six analysed samples yielded zircon U–Pb crystallization ages between 480 and 500 Ma, which support the existence of the early Palaeozoic magmatism in the Dinggye area, central Himalaya. High δ 18 O values (7–10‰, >> a mantle value of 5.3 ± 0.6‰) of magmatic zircon domains and abundant inherited zircons with variable ages (558‐2523 Ma) indicate that the magma was derived from a supracrustal source. Combined with whole‐rock Sr–Nd data (average εNd(t) = −8.1) published previously, we suggest that the granitic gneiss originated from partial melting of old crust, most likely to be the sedimentary rocks of the Himalayan Crystalline Complex. The early Palaeozoic granitic gneiss with a continental arc affinity may have formed in an Andean‐type orogeny involving subduction of the Proto‐Tethyan Oceanic crust beneath the northern margin of the Gondwana supercontinent.